INTEGRASI NILAI ISLAMI, ILMIAH, DAN MEMBAHAGIAKAN DALAM KEGIATAN PEMBELAJARAN DI SDIT ALAM NURUL ISLAM YOGYAKARTA - Rahma Setya Bekti; Ristiyana; Riski Bahtiar; Febriana Devista Nurul Cahyani; Ilham Farizar; Veronika Juliana Heatubun; Aulia Winda Asmara; Taufik Muhtarom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This issue is important to investigate because the integration of Islamic values, scientific values, and joyful learning in primary education is still rarely examined comprehensively, even though these three components are needed to address learning practices that remain overly focused on cognitive aspects. This study aims to identify: (1) the integration of Islamic values in learning activities, (2) the integration of scientific values in learning activities, and (3) the school’s efforts in creating joyful learning experiences at SDIT Alam Nurul Islam Yogyakarta. The study employs a descriptive qualitative method with data analysis based on the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity is ensured through methodological triangulation by comparing the results of observations, interviews, and documentation. The research was conducted on October 28, 2025, at SDIT Alam Nurul Islam Yogyakarta. The findings show that Islamic values are integrated through linking subject matter to the concept of tawhid, daily worship routines, and character development. Scientific values are integrated through observation, simple research activities, and nature exploration. Joyful learning is supported through flexible learning spaces, varied learning models, and a safe and humanistic environment. The integration of these three values forms a holistic educational model that supports students’ spiritual, cognitive, emotional, and social development.